Imaging characteristics of infantile fibrosarcoma. Issue 7 (July 2022) - Eleti, S.; Meshaka, R.; McHugh, K.; Sebire, N.; Tahir, N.
Abstract : Aim: To highlight the imaging findings in a case series of histologically confirmed infantile fibrosarcoma (IF) and identify any features specific to this entity. Materials and methods: Retrospective identification was undertaken of patients with histologically confirmed IF from the electronic patient databases of two institutions between 1 January 2010 and 1 May 2021. Available pre-treatment imaging, histopathological reports, and clinical records were reviewed. Results: Eighteen patients with IF met the inclusion criteria. There were 10 male and eight female patients with a mean age at presentation of 3 weeks. All patients had the t (12; 15) chromosomal translocation. Eleven (61%) tumours were located in the extremities, three were in the craniofacial region, two were intrathoracic, one abdominal and one paraspinal. A single patient had extensive metastases. The tumours were generally isointense to skeletal muscle on T1-weighted sequences and hyperintense on T2 with heterogeneous enhancement and high cellularity seen as diffusion restriction. Fifteen of the 18 lesions were evaluated on ultrasound and appeared as heterogeneous, hypervascular solid or mixed solid/cystic masses, mimicking benign vascular lesions in two cases. Conclusion: The present two-centre, retrospective study of the largest case series described thus far demonstrates that IF is always highly cellular on magnetic resonance imaging but has no other specific imaging features. It should be considered in the differential diagnosis of any enlarging soft-tissue, solid mass arising in the limbs or neck at birth or in infancy. Highlights: Infantile fibrosarcoma is a rare paediatric soft tissue sarcoma. MR is necessary to diagnose IF as this always presents as a highly cellular mass. It should be suspected in infants with a large limb or craniofacial mass.